2012
DOI: 10.1016/j.jssc.2011.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nanoapatites organofunctionalized with aminotriphosphonate agents

Abstract: Organofunctionalized apatite nanoparticles were prepared using a one step process involving dissolution/precipitation of natural phosphate rock and covalent grafting of nitrilotris(methylene)triphosphonate (NTP). The synthesized materials were characterized by Brunauer–Emmett–Teller (BET) surface measurement, thermogravimetry, inductively coupled plasma emission spectroscopy (ICP-ES), elemental analysis, multinuclear solid state cross-polarization/magic angle spinning (CP/MAS) and single-pulse NMR spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The different protonated and complex forms after dehydration have been also investigated by means of 31 P solid-state NMR [33]. Moreover 31 P solid-state NMR, and in particular 31 P isotropic chemical shift, has been exploited for obtaining structural information on possible complexes between NTMPA and tin [34], calcium [35,36] and zirconium-titanate [37] in several organic-inorganic hybrid systems. To the best of our knowledge NMR studies on condensation of NTMPA P-OH groups have not been reported yet, while this and other structural and dynamic properties have been investigated in several works, mainly based on 31 P and 1 H solid-state NMR experiments, on polymeric organic phosphonic acids for applications in proton exchange membranes fuel cells [10,11,38,39], layered microporous tin biphosphonates [40] and mesoporous silica functionalized with phosphonic acids [41].…”
Section: Thermal Behaviormentioning
confidence: 99%
“…The different protonated and complex forms after dehydration have been also investigated by means of 31 P solid-state NMR [33]. Moreover 31 P solid-state NMR, and in particular 31 P isotropic chemical shift, has been exploited for obtaining structural information on possible complexes between NTMPA and tin [34], calcium [35,36] and zirconium-titanate [37] in several organic-inorganic hybrid systems. To the best of our knowledge NMR studies on condensation of NTMPA P-OH groups have not been reported yet, while this and other structural and dynamic properties have been investigated in several works, mainly based on 31 P and 1 H solid-state NMR experiments, on polymeric organic phosphonic acids for applications in proton exchange membranes fuel cells [10,11,38,39], layered microporous tin biphosphonates [40] and mesoporous silica functionalized with phosphonic acids [41].…”
Section: Thermal Behaviormentioning
confidence: 99%
“…Hydroxyapatite Ca 10 (PO 4 ) 6 (OH) 2 (HAp) is a naturally occurring mineral widely used in development of bioceramics, environmental sorbents and heterogeneous catalysis [1][2][3][4]. Its reactivity depends on different parameters such as particles size, porosity and crystallinity [5][6][7]. In recent years, several studies have shown that the addition of a wide range of additives, such as silane [8] and titanate coupling agents [9], biomacromolecules [10] and polymers [11] can control the nucleation of hydroxyapatite and modify its surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…(Douard et al 2010). Finally, a small loss was observed between 600 and 00 ºC assigned to the departure of water during structural transformation (Saoiabi et al 2012). The amount of PCL grafted on HAp was measured directly from the TGA curves, since it corresponds to the weight loss [%] in the range 200 -400 ºC as reported in the Table 1.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%